Localized axillary milia en plaque: a rare cutaneous case presentation of systemic amyloidosis. (1st October 2016) - Dickison, P.; Howard, V.; Wylie, B.; Smith, S. D.
Summary : Systemic AL amyloidosis is known to be associated with plasma cell dyscrasias, including multiple myeloma. The cutaneous manifestations of systemic AL amyloidosis are varied, but typically include waxy plaques or subcutaneous nodules. We report a woman who presented with bilateral eruptions of hyperpigmented plaques in her axillae, which were diagnosed as milia en plaque. She had a history of multiple myeloma, for which she was under the care of a haematologist. This is the first documented case, to our knowledge, of an eruption in the axillae being milia en plaque.